Experimenting in Somalia: The new security empire. (September 2017) - Besteman, Catherine
The past several decades of US intervention in Somalia produced violent destabilization, dysfunction, and uncertainty, creating refugee outflows and terrorist networks against which the US is currently tightening its security cordons. This paper argues that Somalia's recent history as a stateless region offers a cautionary and tragic case study of the long-term damages that ensue when wealthy states that intervene in poorer states in the name of their own security instead cause insecurity and inequities that enable violence, and then in response to that violence enact further securitization to protect themselves against the consequences of that damage. But rather than focusing on the state as a site of securitization, I focus on those whose lives are made insecure by the retreat of their state government and the imposition in its place of security regimes that are not created by their own state government. Such security regimes overlap and compete, are instituted by different state and nonstate actors for different purposes, and by their incoherence and multiplicity raise questions about the definition, location, and relevance of the state in such regions. The paper explores the emergence of new, interlinked security regimes that are partially or wholly constituted through the logics of a new security empire designed to respond to US security concerns. By turning attention to the situations faced by those who live within the insecurities of stateless regions, the paper asks, what happens to the concept of securitization when the national-territorial state is not the entity that operates as a 'state' in the lives of people, even though their lives are overlain with multiple and overlapping regimes of securitization?